Fundy Tidal Power Environmental Sedimentology - Yeo, R.; Risk, M. (Geoscience Canada, 1979)
Summary Tidal power potentially can contribute significantly to North America's future needs. Proposed developments in the upper reaches of the Bay of Fundy have a total generating capacity half again that of Niagara Falls. Construction of tidal power barrages could, however, have serious consequences to the marine environment. The high productivity of the mtertidal communities in the upper reaches is maintained in part by tidal flushing; these communities are also affected by changes in sediment type. The upper reaches are important feeding areas for migratory shorebirds and commercial species of fish, and may function as a nursery estuary, supporting offshore fisheries. Serious siltation problems could also shorten the lifespan of tidal power barrages- It is questionable whether studies now underway to assess the consequences of development can gather the necessary data within the allotted time frame Computer simulation of sediment dynamics combined with programs designed to assess the effect of siltation on benthic communities will, probably within a year, allow estimates of expected productivity losses to be made for some of the areas which have already been studied.